Perkembangan dan Pola Struktur Perekonomian Sektor Pertanian Kabupaten Padang Pariaman - Nuraini Nuraini; Syahrial Syahrial; Angelia Leovita (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
The agricultural sector is the second largest contributor to the PDRB of Padang Pariaman Regency, but thecontribution of the agricultural sector to the economy is decreasing. A number of food, horticultural andplantation commodity crops experienced a decline in production from 2016-2020. This study aims toanalyze the development, patterns and economic structure of the agricultural sector in Padang PariamanRegency. This research was conducted in Padang Pariaman Regency, West Sumatra. This study uses 3agricultural sub-sectors, namely the food crops sub-sector, horticultural crops sub-sector and plantationcrops sub-sector. The data used in this research is secondary data consisting of production data. The methodused in this research is quantitative. The data sources used in this study came from the Central Bureau ofStatistics for Padang Pariaman Regency, the Central Statistics Agency for West Sumatra Province and thePadang Pariaman Regency Agriculture Office in 2016-2020. The data analysis technique used is theDiversity Entropy Index and the Klassen Typology. The results of the study can be concluded that the IDEvalue for all commodities in the agricultural sub-sector of Padang Pariaman Regency is <1, which means itis not growing or evenly distributed. The results of the Klassen Typology analysis are that there are sixcommodities that are classified as advanced and fast-growing commodities and fast-growing commodities.There are eight commodities that are classified as advanced but under pressure and commodities that arerelatively underdeveloped. Therefore, the government of Padang Pariaman Regency needs to make policiesthat can support increased activity in the agricultural sector, improve technology and innovation so thatproductivity increases and commodity equity.